Pemanfaatan Media Sosial sebagai Media Dakwah di Era Digital - Muhammad Badrul Munir (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2019)
This paper aims to explain the trend of preaching in the digital era through the use of social media. This medium encourages preachers, particularly millennials, to create Islamic content presented casually through daily life stories and humor. This strategy has proven effective with millions of viewers on YouTube. Da'wah is an activity aimed at inviting others to goodness, while media serves as a tool for delivering the message. An-Nawawi Berjan Islamic Boarding School in Purworejo is an example of implementing modern da'wah strategies by utilizing Instagram and YouTube, targeting millennials with contemporary images and videos. This approach responds to the increasing prevalence of radical social media accounts that easily declare things forbidden without proper application of Islamic legal principles.